Differentiation Strategies for Arabic Language Learning in the Context of the Independent Curriculum: A Solution for Diverse Student Abilities: Strategi Diferensiasi Pembelajaran Bahasa Arab dalam Konteks Kurikulum Merdeka: Solusi untuk Keberagaman Kemampuan Siswa - Nur Iman, Muhammad; Faedurrohman, Faedurrohman (ELOQUENCE : Journal of Foreign Language, 2024)
Background: The process of teaching Arabic in Indonesian schools is quite a complicated challenge for teachers, especially when faced with differences in student abilities that require adjusting the teaching model. Purpose: This study aims to analyze the application of differentiation strategies in Arabic language learning within the framework of the Merdeka Curriculum through a review of available literature, as well as identify challenges and opportunities for success as reflected in the results of previous studies. Methods: This research uses a literature study approach, in which researchers review existing literature to collect, analyze, and summarize information related to differentiation strategies in Arabic language learning and the implementation of the Merdeka Curriculum. Results and Discussion: The results show that differentiation strategies contribute significantly to learning effectiveness, improving student engagement and learning outcomes. However, challenges such as limited time, resources and institutional support remain. This research provides guidance for teachers and policy makers to design more inclusive and effective learning. Conclusions and Implications: The conclusion of this study shows that differentiation strategy significantly contributes to improving the effectiveness of Arabic language learning. In its implementation, this strategy has a positive impact on the aspect of increasing students' engagement and their learning outcomes, especially in adjusting their very diverse abilities and learning styles. In addition, the role of technology is very important in supporting the process of implementing differentiation strategies, although the limitations of time and resources remain a major challenge in its implementation. The implications of implementing differentiation strategies from both theoretical and practical perspectives indicate the need to develop new learning models and teacher training programs.